2016
DOI: 10.1042/bcj20160148
|View full text |Cite
|
Sign up to set email alerts
|

The ADAMTS hyalectanase family: biological insights from diverse species

Abstract: The a disintegrin-like and metalloproteinase with thrombospondin type-1 motifs (ADAMTS) family of metzincins are complex secreted proteins that have diverse functions during development. The hyalectanases (ADAMTS1, 4, 5, 8, 9, 15 and 20) are a subset of this family that have enzymatic activity against hyalectan proteoglycans, the processing of which has important implications during development. This review explores the evolution, expression and developmental functions of the ADAMTS family, focusing on the ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 148 publications
0
19
0
Order By: Relevance
“…We focussed on expression of specific ECM components identified as up-regulated, and used quantitative PCR to confirm the changes in expression detected by RNA-seq. PCR analysis of RNA isolated from new MEF preparations confirmed that message levels for fibrillin 2 (which forms elastic microfibrils within the ECM [ 38 ]), adamts15 (a matrix-associated peptidase [ 39 ]), and FRAS1 (Fraser extracellular matrix complex 1 –an ECM component abundant in basement membrane [ 40 ]), are all highly up-regulated in CAV1-/- MEFS ( Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We focussed on expression of specific ECM components identified as up-regulated, and used quantitative PCR to confirm the changes in expression detected by RNA-seq. PCR analysis of RNA isolated from new MEF preparations confirmed that message levels for fibrillin 2 (which forms elastic microfibrils within the ECM [ 38 ]), adamts15 (a matrix-associated peptidase [ 39 ]), and FRAS1 (Fraser extracellular matrix complex 1 –an ECM component abundant in basement membrane [ 40 ]), are all highly up-regulated in CAV1-/- MEFS ( Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypes induced by the adamts5 morphants were rescued with mRNA encoding both wild-type and catalytically-inactive ADAMTS5. Although unexpected, there is some precedence for ADAMTS family members demonstrating non-catalytic functions as reviewed recently [ 35 ]. For example, ADAMTS1 has been shown to bind to VEGF through its C-terminal thrombospondin repeats and spacer domain to block VEGFR2 activation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ADAMTSs are a family of secreted proteins that is composed of 19 members in mammals [60,61]. ADAMTSs are involved in a wide variety of physiological and pathological processes that include, among other things, their participation in the degradation and thus the remodeling of components of the extracellular matrix, the inhibition of angiogenesis, and the regulation of inflammatory processes [61,62].…”
Section: Adamtss In the Cnsmentioning
confidence: 99%